INVESTIGATION OF A CRIME SCENE WITH TWO VICTIMS AND A PERPETRATOR THROUGH DNA TRACES - Andrade, Marina; Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
To deal with crime identification problems, that are examples of situations in which forensic approach the DNA profiles is frequent, it is needed an introduction to present and explain the various concepts involved . So the use of object-oriented Bayesian netwoks (OOBN), examples of probabilistic expert systems (PES), is shown an exemplified.